PENGARUH CITRA ORGANISASI, PENETAPAN HARGA, KUALITAS LAYANAN TERHADAP KEPUASAN MAHASISWA DAN DAMPAKNYA PADA LOYALITAS MAHASISWA - Deri Deri; Amri Amri; Zufriady Zufriady (JEM Jurnal Ekonomi dan Manajemen, 2018)
The competition that always arises in the business world encourages the emergence of new thoughts that can build products or services that provide more value to customers. This study aims to examine the effect of the organizational image, pricing, service quality on student satisfaction, the sample in this study were 193 students. Path analysis is used to test the relationship between variables in the form of causality. The results of the study concluded that there were significant effects of organizational image variables, pricing, and service quality simultaneously on student satisfaction. However, partial testing shows that the only service has a significant effect on student satisfaction. The results of this study should be a reference for researchers who will conduct further research. In addition, it is also necessary to learn more about other independent and bound variables to examine.